The factors that influence employability skills of vocational school student mechanical engineering - Muhammad Noor Fitriyanto; Pardjono Pardjono (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aimed to find out the significance of the direct effect of industrial work practices on work readiness, vocational competency, and employability skills, the direct effect of work readiness on employability skills, and the direct effect of vocational competency on employability skills. Furthermore, it was to find out the significance of the indirect effect of industrial work practices on employability skills through work readiness, indirect effect of industrial work practices to employability skills through vocational competency. The significance of the effect founds was expected to enhance the knowledge and consideration for developing employability skills vocational high school (VHS) students especially at industrial work practice, work readiness, vocational competency at vocational high school. The research used quantitative approach with ex-post facto type. The data were analyzed quantitavely to test the formulated hypotesis. The research was conducted at State and Private Vocational High School in DIY. The study population was grade XII students majoring in mechanical engineering. The research samples were 444 student who were selected using proportionate stratified random sampling. The data collection techniques were questionnairies distribution and documentation. The content validity was established using expert judgment. The construct validity was establised using analysis factor by Kaiser Meyer Olkin Measure of Sampling Adequacy (KMO MSA) with value of 0.691. The reliability of the research was judged using cronbachs alpha with value for work readiness of 0.921 and employability skills of 0.864. The data analysis technique used path analysis. The result showed that (1) direct effect of industrial work practice on work readiness was found with r 23.3%, (2) direct effect of industrial work practices on vocational competency was found with r 28.2%, (3) direct effect of work readiness on employability skills was found with r 10.1%, (4) direct effect of work readiness on employability skills was found with r 50.1%, (5) direct effect of vocational competency on employability skills was found with r 15.4%, (6) indirect effect of industrial work practices on employability skills through work readiness was found with r 11.7%, (7) indirect effect of industrial work practices on employability skills through vocational competency was found with r 4,3%. Employability skills can be improved through effective implementation of industry work practice, work readiness, and vocational competency.